Reduced graphene oxide/VSB-5 composite micro/nanorod electrode for high energy density supercapattery. (20th September 2021) - Raihana, M.K.; Padmanathan, N.; Eswaramoorthi, V.; McNulty, David; Sahadevan, Jhelai; Mohanapriya, P.; Muthu, S. Esakki
Highlights: Well-dispersed novel zeotype VSB-5 and VSB-5/rGO composites were fabricated. Investigated as a superior battery-type electrode for Supercapatteries. Supercapattery exhibits high energy of 80.5 Whkg−1 at a power output 2216.5 Wkg−1. Device with VSB-5/rGO shows good cyclic stability for long term applications. Abstract: Nickel Phosphate (Ni20 [(OH)12 (H2 O)6 ][(HPO4 )8 (PO4 )4 ]12H2 O) – VSB-5 nano/micro rods composite with reduced graphene oxide (rGO) was successfully synthesized using a Polyvinyl Pyrrolidone (PVP) aided hydrothermal technique and applied as a battery-type cathode for supercapatteries. The uniform meso/microporous structure provides more electro-active sites for surface redox reaction and nano-paths for electrolyte ion diffusion which can significantly improve the device performance. From the electrochemical analysis, it was found that VSB-5/rGO exhibited a specific capacity of 117.3 mAh g −1 (1056.1 F g −1 ) which was noticeably higher than the pristine VSB-5 (60.7 mAh g −1 ) at 5 mA cm −2 . These excellent electrochemical performances may be due to rGO modification and well-defined nano/micro rods. Furthermore, supercapatteries were fabricated by pairing a commercially available activated carbon (AC) electrode with VSB-5/rGO as a positrode. The fabricated cell was tested and showed a high specific capacity of 86.8 mAh g −1 (208.4 F g −1 ) with 88% capacity retention after 5000 cycles. Finally, the assembled supercapattery delivered a maximum specific energy of 80.5 Wh kg −1 at a power output of 2216.5 W kg −1 . In comparison with a pristine VSB-5 based device, the AC/VSB-5/rGO device shows remarkable electrochemical performance, demonstrating that VSB-5/rGO is a promising, new electrode material for high performance supercapatteries. Graphical abstract: Image, graphical abstract